AÇÕES DE EDUCAÇÃO AMBIENTAL NA INSTALAÇÃO DE UMA USINA HIDRELÉTRICA NA REGIÃO NOROESTE DO RS - Vitcel, Marlise Sozio; Nishijima, Toshio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
This study aimed to study environmental education in the installation of a hydroelectric powerplant in northwestern of Rio Grande do Sul, Brazil. From the theoretical reflection: the energy andenvironmental issues, sustainable development and environmental education in this process, thisresearch examined the proposal for environmental education implemented in the process of installingthe hydroelectric San Jose, with regard to its purpose and its effectiveness. The research ischaracterized by its qualitative nature, being in an exploratory and descriptive. As for the meansemployed to this investigation, the literature search, the primary data collection that occurredthrough interviews and secondary sources consulted in the documents of the hydroelectric plantand official sites. The data was made by content analysis. The research is also characterized as acase study. Outlining the discussions of power generation, it appears that the hydroelectric play animportant role, given its ability to generate action and the fact it is one of the cleanest - as compa- red to fossil fuels, for example - however, not discusses why energy demand is ever increasing, notdiscussing the rational and efficient use of energy. From reflections on the theoretical frameworkand analysis of the environmental education program developed by the project studied, it is clearthat environmental education was an important part in the context of building the dam and in thelist of environmental programs developed.